Perceived Effect of Open Access Institutional Repositories on the Research Activities of Academic Staff in Some Selected Federal Universities in North-East Nigeria (NAU Journal of Library and Information Science, 2023)
The study examined the perceived effect of open-access institutional repositories on the research activities of academic staff in some selected federal universities in North-East Nigeria. It adopted a survey design using three (3) federal universities in three (3) States ofthe zone, purposively selected. Four null hypotheses were employed to guide the study. 363 academic staff were sampled from a total study population of 3,631 using the multi-stage sampling technique. Data was collected using a questionnaire. 363 copies of thequestionnaire were distributed but 337 were returned. Mean and standard deviation were used to answer the research questions while t-test statistics were used to test the null hypotheses at a 0.05 level of significance. The study found a high level of awareness and ahigh extent of utilization of OAIRs. It also revealed numerous perceived effects of OAIRs on the academic staff’s research activities, with different strategies for enhancing the functionality of OAIRs in federal universities in North-East Nigeria and beyond. However, based on the findings, the study recommended that the National Universities Commission should intensify efforts in organizing seminars, workshops, and symposiums on the issue of OAIRs and ways in which academic staff can utilize and enjoy its usefulness.
Keywords: Institutional Repositories; OAIRs, Universities, Research, Effects